EXAMINING CHALLENGES AND SOLUTIONS FOR WOMEN ENTREPRENEUR: A LITERATURE REVIEW - I Gusti Ayu Diah Werdhi Srikandi Wedasteraputri Suyasa; Wayan Ardani (Universitas Mahendradatta, 2026)
Women entrepreneurs play a critical role in promoting innovation, economic growth, and job creation. However, they face significant challenges, including limited resources, cultural and societal barriers, legal and regulatory issues, and limited access to professional networks. The purpose of this study is to provide a thorough analysis of the problems, challenges, and success factors associated with women entrepreneurs. Relevant literature from scholarly databases, official documents, and international organizations was subjected to a qualitative content analysis. The systematic literature review (SLR) of women's empowerment publications published in different journals between 2016 and 2026. Significant barriers, such as gender-based discrimination and restricted access to financial resources, were identified in this study along with success factors including education, advancements in technology, and strong support systems. In order to foster an inclusive entrepreneurial climate, the research emphasizes the need for targeted regulations, funding, and mentorship programs. The result of this study can be as reference for policymakers, financial institutions, and business development organizations to design initiatives that support women entrepreneurs. The novelty of this study is a policy-action mapping, prioritizes a range of policy levers (such as targeted financing, mentorship programs, regulatory simplification, and training in digital skills) and links each one with evidence of probable impact.